Pelvic restraint cushion sled test evaluation of pelvic forward motion. (3rd April 2018) - Shaw, Greg; Lessley, David; Ash, Joseph; Acosta, Salvador; Heltzel, Sara; Riley, Patrick; Kim, Taewung; Crandall, Jeff
ABSTRACT: Objective : This study was designed to evaluate the performance of a pelvic restraint cushion (PRC), a submarining countermeasure that deploys under the thighs when a crash is detected in order to block the forward motion of the pelvis. Methods : Sled tests approximating low- and high-speed frontal impacts were conducted with 4 female postmortem human subjects (PMHS) restrained by a lap and shoulder belt in the right front passenger seat. The subjects were tested with and without a PRC. Results : The PRC is effective in reducing forward motion of the PMHS pelvis and reduces the risk of injury due to lap belt loading in a high-speed frontal crash. Conclusions : Although small sample size limits the utility of the study's findings, the results suggest that the PRC can limit pelvic forward motion and that pelvic injury due to PRC deployment is not likely.